THE RISKS OF INTRODUCTION OF MODERN TECHNOLOGIES IN THE EDUCATIONAL PROCESS OF THE COLLEGE - D. Smolyakova (Вестник университета)
The risks of introduction of modern technologies in the educational process of the College on the example of «Sevastopol College of service and trade» have been investigated. A number of contradictions in the course of technologization of vocational education has been highlighted. The main goals and objectives of the application of new technologies in the College have been adduced. The list has been presented and new technologies, using in the educational process of the College, have been described. Organizational and financial risks of introduction of modern technologies in the educational process of the College have been substantiated.